HUBUNGAN STATUS GIZI DENGAN KECACINGAN PADA SISWA SDN 1 PAHANDUT SEBERANG KOTA PALANGKA RAYA - Agnes Immanuela Toemon; Arini Ratnasari; Desi Rahma Maulia; Friska Merilia Dwi Kristiani; Indria Augustina; Arif Rahman Jabal; Ni Nyoman Sri Yuliani (Poltekkes Kemenkes Pakassar, 2023)
Parasitic worm infections can affect the concentration of elementary school students in receiving lessons at school. This study aimed to determine the relationship between nutritional status and helminthiasis infecting elementary school children in grades 1-3 at SDN 1 Pahandut Seberang. Examining the presence of worm eggs includes measuring body weight and height, fecal sampling, feces processing using the Kato-Katz method, and identification of worm eggs. The results of this study are the highest characteristics of elementary school children, namely those with poor nutritional status. The distribution of parasitic worm species found were Ascaris lumbricoides and Trichuris trichiura. The highest prevalence of parasitic worms, namely Ascaris lumbricoides, was 71.7%. The intensity of worms most commonly found was Ascaris lumbricoides at 57.8%. The nutritional status of elementary school children with an undernutrition status of 36.0% is closely related to the prevalence and intensity of worms at SDN 1 Pahandut Seberang.